Domestic Contracts and Family Law Exceptionalism: An Historical Perspective - Taylor, Luke (McGill Law Journal / Revue de droit de McGill, 2020)
Since at least the late 1980s, the enforceability of domestic contracts in Canadian common law has tended to be analyzed in terms of a formal equality/substantive fairness dichotomy. This paper suggests that our understanding of the common law of domestic contracts in Canada can be enriched by adding an historical lens to existing analyses. Specifically, the paper argues that the Supreme Court of Canada’s decision in the Pelech v. Pelech trilogy was not only an attempt to inject the ideology of contract into family law, but also amounted to a continuation of long-standing approaches to separation agreements in English and Canadian law—an approach that rendered the treatment of separation agreements and the result in Pelech historical outliers when considered against broader exceptionalizing trends in judicial and scholarly approaches to agreements touching upon the family. From this perspective, the retreat from Pelech in the subsequent Supreme Court of Canada cases of Miglin v. Miglin, Hartshorne v. Hartshorne, and Rick v. Brandsema was, therefore, also a move away from the historically distinctive approach to separation agreements, and the continuation of much older processes of exceptionalism within family law.